Impact of epidemic outbreaks (COVID-19) on global supply chains: A case of trade between Turkey and China. (February 2023) - Kazancoglu, Yigit; Ekinci, Esra; Mangla, Sachin Kumar; Sezer, Muruvvet Deniz; Ozbiltekin-Pala, Melisa
Abstract: COVID-19 has negative impacts on supply chain operations between countries. The novelty of the study is to evaluate the sectoral effects of COVID-19 on global supply chains in the example of Turkey and China, considering detailed parameters, thanks to the developed System Dynamics (SD) model. During COVID-19 spread, most of the countries decided long period of lockdowns which impacted the production and supply chains. This had also caused decrease in capacity utilizations and industrial productions in many countries which resulted with imbalance of maritime trade between countries that increased the freight costs. In this study, cause and effect relations of trade parameters, supply chain parameters, demographic data and logistics data on disruptions of global supply chains have been depicted for specifically Turkey and China since China is the biggest importer of Turkey. Due to this disruption, mainly exports from Turkey to China has been impacted in food, chemical and mining sectors. This study is helpful to plan in which sectors; the actions should be taken by the government bodies or managers. Based on findings of this study, new policies such as onshore activities should consider to overcome the logistics and supply chain disruptions in global supply chains. This study has been presented beneficial implications for the government, policymakers and academia. Highlights: The COVID-19 affects the global supply chain worldwide. This study aims to evaluate the sectoral impacts of Epidemic outbreaks (COVID – 19) on global supply chains. The proposed SD Model is helpful to plan in which sectors; the actions should be taken by the government bodies or managers. Disruptions caused by COVID-19 in global supply chains negatively affects trade and logistics activities between countries. This study presents implications for policymakers and managers by revealing which sectors will be impacted by the pandemic.